Analisis Wacana Tutur Tingkah Dadi Wwang - Kuna Winaya, Ni Wayan Putri; Sukartha, I Nyoman; Suastika, I Made (Humanis, 2017)
This research tells the story that contains the teaching of bhakti. This study posed two problems (1) the structure of discourse contained in the script, and (2) function and meaning contained it. The theoretical basis that isued to solve the problem used a theoretical basis, is critical discourse, semiotics, and the theory of functions. At the stage of data collection used method of reading the manuscript with the help of the techniques of note. Analyzing the data used descriptive analytic method with species selection techniques were then adapted to the object of study. Then at the stage of presentation of the resultof the analysis used formal and informal methods, are aquipped with deduktive and inductive thinking techniques
Keywords: tutur, discourse, tingkah, wwang